Plasticity-related microRNA and their potential contribution to the maintenance of long-term potentiation - Ryan, Brigid; Joilin, Greig; Williams, Joanna M. (Frontiers in Molecular Neuroscience, 2015)
Long-term potentiation (LTP) is a form of synaptic plasticity that is an excellent model for the molecular mechanisms that underlie memory. LTP, like memory, is persistent, and both are widely believed to be maintained by a coordinated genomic response. Recently, a novel class of non-coding RNA, microRNA, has been implicated in the regulation of LTP. MicroRNA negatively regulate protein synthesis by binding to specific messenger RNA (mRNA) response elements. The aim of this review is to summarize experimental evidence for the proposal that microRNA play a major role in the regulation of LTP. We discuss a growing body of research which indicates that specific microRNA regulate synaptic proteins relevant to LTP maintenance, as well as studies that have reported differential expression of microRNA in response to LTP induction. We conclude that microRNA are ideally suited to contribute to the regulation of LTP-related gene expression; microRNA are pleiotropic, synaptically-located, tightly regulated, and function in response to synaptic activity. The potential impact of microRNA on LTP maintenance as regulators of gene expression is enormous.